1972
DOI: 10.2307/1239170
|View full text |Cite
|
Sign up to set email alerts
|

Trend Models of Feeder, Slaughter, and Wholesale Beef Cattle Prices

Abstract: Harmonic regressions were fitted to monthly data to provide a low cost alternative means of predicting prices at three market levels in the beef industry and to provide information on time interrelationships among these market levels. The results have limited prediction potential and support preconceived ideas concerning time interrelationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

1979
1979
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 2 publications
1
8
1
Order By: Relevance
“…However, farm and wholesale value changes had their strongest association at a zero lag in the present analysis. These results sharply contradict the conclusion of Franzmann and Walker [5] that wholesale prices lead farm prices by three months.…”
Section: An Applicationcontrasting
confidence: 77%
See 2 more Smart Citations
“…However, farm and wholesale value changes had their strongest association at a zero lag in the present analysis. These results sharply contradict the conclusion of Franzmann and Walker [5] that wholesale prices lead farm prices by three months.…”
Section: An Applicationcontrasting
confidence: 77%
“…With respect to frequency domain techniques, harmonic analysis is sometimes used to assess leadlag relationships [5]. However, it is not possible, in a mathematical sense, to distinguish between a lead and a lag by that technique [1, p. 311].…”
Section: Univariate Residual Cross-correlation Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Kulshreshtha and Wilson (1973) found two beef price cycles for Canada: a 12-month cycle similar to the one obtained by this study, and a longer cycle of nine and a half years. Franzmann and Walker (1972), Mundlak and Huang (1996), and Stockton and (2007) found that the U.S. beef price cycle had a period of 10 years, similar to the U.S. inventory cycle. The beef price cycle runs counter to and leads both inventory and beef supply cycles.…”
Section: Nature Of Cyclesmentioning
confidence: 92%
“…They achieved highly significant coefficient estimates and an R-squared statistic of .958. Franzmann and Walker (1972) achieved similarly impressive results for identifying cattle cycles over the period 1925-1969 employing trigonometric model formulations utilizing prices received and average costs per hundredweight for feeder cattle and slaughter cattle. Additionally, wholesale beef prices were successfully used to estimate cycles over the period 1949to 1969.…”
Section: Explaining Livestock Cyclesmentioning
confidence: 96%